2020
DOI: 10.1371/journal.pone.0234395
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs underpin nutrition components in aromatic rice germplasm

Abstract: As rice is an important staple food globally, research for development and enhancement of its nutritional value it is an imperative task. Identification of nutrient enriched rice germplasm and exploiting them for breeding programme is the easiest way to develop better quality rice. In this study, we analyzed 113 aromatic rice germplasm in order to identify quantitative trait loci (QTL) underpinning nutrition components and determined by measuring the normal frequency distribution for Fe, Zn, amylose, and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
(49 reference statements)
1
3
0
Order By: Relevance
“…Clusters IV and VI are solitary clusters. Similar results were observed by Islam et al (2020), as they used 113 rice genotypes for D 2 -analysis and observed that these genotypes were grouped into 4 clusters. Diversity analysis by Tejawini et al (2018) and Salem and Sallam (2016) have also shown similar findings.…”
Section: Diversity Analysis Using Morphological Datasupporting
confidence: 83%
“…Clusters IV and VI are solitary clusters. Similar results were observed by Islam et al (2020), as they used 113 rice genotypes for D 2 -analysis and observed that these genotypes were grouped into 4 clusters. Diversity analysis by Tejawini et al (2018) and Salem and Sallam (2016) have also shown similar findings.…”
Section: Diversity Analysis Using Morphological Datasupporting
confidence: 83%
“…Most of the QTLs for Fe and Zn content were identified through single-nucleotide polymorphism (SNP) and DArT-SSR markers in RIL and BIL populations, but some of them were also from DH lines ( Table 1 ). Recently, many new QTLs for Fe and Zn content have been mapped mainly through SSR markers in DH and BIL mapping populations ( 26 , 27 , 29 , 34 36 ) ( Table 1 ). Maize hybrids and varieties having a high yield potential along with 25–30% more Fe and Zn than common cultivars have been developed as part of the HarvestPlus program ( 108 ).…”
Section: Introductionmentioning
confidence: 99%
“…This locus has been frequently reported from aus derived populations. Several studies have also identified similar genomic regions ( Lu et al., 2008 ; Garcia-Oliveira et al, 2009 ; Zhang et al., 2014 ; Descalsota-Empleo et al., 2019b ; Islam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 89%